Cytokine Expression Profile in Aqueous Humor and Sera of Patients with Acute Anterior Uveitis - Chen, W.; Zhao, B.; Jiang, R.; Zhang, R.; Wang, Y.; Wu, H.; Gordon, L.; Chen, L. (Current Molecular Medicine, 2015)
Purpose: To evaluate cytokine expression profile in aqueous humor and sera in patients with HLAB27 associated acute anterior uveitis (AAU) and idiopathic AAU. Methods: Twenty patients with AAU and 17 controls were recruited from August 2012 to March 2013. Study subjects with uveitis were divided into two groups: 9 patients with idiopathic AAU and 11 patients with HLA-B27 associated AAU. Complete ophthalmological examinations were performed and clinical features of each group were clearly documented. Aqueous humor and sera were collected and the concentration of 15 immune mediators (IL-1β, IL-4, IL-6, IL-10, IL-17A, IL-17F, IL-21, IL-22, IL-23, IL-25, IL-31, IL-33, TNF-α, IFN-γ, sCD40L) were measured in both aqueous humor and sera simultaneously by multiplex immunoassay. Results: There were significantly higher levels of multiple cytokines in aqueous humor in patients with uveitis compared to controls, including IL-1β, IL-6, IL-10, IL-17a, IL-17f, IL-21, IL-25, IL-31, IFN-γ, TNF-α, and sCD40L. The levels of IL-17a in aqueous humor correlated significantly with disease activity in patients with idiopathic AAU, while the level of IFN-γ in aqueous humor correlated significantly with disease activity in patients with HLA-B27 associated AAU. There was no significant difference in serum cytokine expression between uveitis patients and controls except IL-6, elevated in patients with both idiopathic and HLA-B27 associated AAU. Conclusion: Cytokine expression pattern in the aqueous humor, in contrast to that in serum, may reflect intraocular immune reactions during active inflammation in patients with AAU. Both Th1 and Th17 are involved in immunopathogenesis of HLA-B27 associated and idiopathic AAU, but a different cytokine pattern was identified in these two clinical entities. A predominant Th17-driven immune response may play an important role in the immunopathogenesis of idiopathic AAU, while Th1 dominant immune response may be responsible for the inflammation in HLA-B27 associated AAU.
Keywords: Anterior uveitis